The anti-inflammatory and antioxidant effects of hydroalcoholic extract of Petiveria alliacea - Zaa, César (2012)
The free radicals and the oxidative damage are related with cellular death, with the lipid peroxidation being a mechanism that leads to oxidative destruction of the cellular membrane. Furthermore, in inflammatory process, one of the first stages is the incremented vascular permeability (formation of the oedema) followed with the extravasation of the fluids, migration of the leucocytes to the damaged site and release of pro-inflammatory proteins. Was evaluated antioxidants and anti-inflammatory of Petiveria alliacea“mucura”. For antioxidants effect, was evaluated formation of thiobarituric acid reactive substances as indicator of lipid peroxidation. Doses 200 mg/mL of Petiveria alliaceadecrease significatly in 42% levels of MDA compared to water (negative control). In the antiinflammatory evaluation, inflammation was analyzed in the carrageenan-induced paw oedema test in mice (solution to 1 %) and in the "carrageenan-induced air-pouch formation" of rates for acute and chronic inflammation respectively. In anti-inflammatory evaluation there is a significant reduction of the edema in 23.26% at 4hrs at the treatment. For chronic inflammation there is a reduction of 25.9% and 29.5% of the weight and volume of exuded extract respectively, as well as a reduction of 24% of weight of fibrous tissue. These results demonstrate antioxidant and anti-inflammatory effects of Petiveria alliacea.